Loss of forest cover and host functional diversity increases prevalence of avian malaria parasites in the Atlantic Forest. Issue 9 (August 2021) - Fecchio, Alan; Lima, Marcos R.; Bell, Jeffrey A.; Schunck, Fabio; Corrêa, Aline H.; Beco, Renata; Jahn, Alex E.; Fontana, Carla S.; da Silva, Thaiane W.; Repenning, Márcio; Braga, Érika M.; Garcia, José E.; et al.
Graphical abstract: Highlights: Avian malaria prevalence increases with deforestation across the Atlantic Forest. Plasmodium prevalence increases with diminishing host functional diversity. Reduction in host functional diversity also increases Plasmodium lineage richness. Plasmodium lineage richness increases with avian host diversity. Landscape anthropogenic changes impact avian malaria prevalence and diversity. Abstract: Host phylogenetic relatedness and ecological similarity are thought to contribute to parasite community assembly and infection rates. However, recent landscape level anthropogenic changes may disrupt host-parasite systems by impacting functional and phylogenetic diversity of host communities. We examined whether changes in host functional and phylogenetic diversity, forest cover, and minimum temperature influence the prevalence, diversity, and distributions of avian haemosporidian parasites (genera Haemoproteus and Plasmodium ) across 18 avian communities in the Atlantic Forest. To explore spatial patterns in avian haemosporidian prevalence and taxonomic and phylogenetic diversity, we surveyed 2241 individuals belonging to 233 avian species across a deforestation gradient. Mean prevalence and parasite diversity varied considerably across avian communities and parasites responded differently to host attributes and anthropogenic changes. Avian malaria prevalence (termed herein as an infection caused by Plasmodium parasites) was higher in deforested sites, and both Plasmodium prevalence and taxonomic diversity were negatively related to host functional diversity. Increased diversity of avian hosts increased local taxonomic diversity of Plasmodium lineages but decreased phylogenetic diversity of this parasite genus. Temperature and host phylogenetic diversity did not influence prevalence and diversity of haemosporidian parasites. Variation in the diversity of avian host traits that promote parasite encounter and vector exposure (host functional diversity) partially explained the variation in avian malaria prevalence and diversity. Recent anthropogenic landscape transformation (reduced proportion of native forest cover) had a major influence on avian malaria occurrence across the Atlantic Forest. This suggests that, for Plasmodium, host phylogenetic diversity was not a biotic filter to parasite transmission as prevalence was largely explained by host ecological attributes and recent anthropogenic factors. Our results demonstrate that, similar to human malaria and other vector-transmitted pathogens, prevalence of avian malaria parasites will likely increase with deforestation.